Pengaruh Mutu Pelayanan Dan Harga Terhadap Kepuasan Pengunjung - Ah Khafid Fiqih A; Budi Wahono; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine the effect of service quality and price on visitor satisfaction, the sample of this study is Mystic Coffee visitors. Data collection using a questionnaire, data analysis using validity test, reliability test, normality test, multiple linear analysis, F statistic test and t statistic test, coefficient of determination test in IBM Social Sciences Statistical Package (SPSS) Version 16.0From the results of calculations with SPSS which is a variable of service quality and price simultaneously and significantly to visitor satisfaction. While partially the service quality and price variables have a positive and significant effect on visitor satisfaction. Keywords: Effect of Service Quality and Price on Visitor Satisfaction